2018
DOI: 10.1016/j.rpor.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of image based brachytherapy using tandem ovoid and tandem ring applicators

Abstract: The results indicate that the OAR doses assessed by DVH criteria were higher than ICRU point doses for the bladder with both tandem-ovoid and tandem-ring applicators whereas DVH based dose was lower than ICRU dose for the rectum. The point B dose, the treated volume and high dose volume was found to be slightly higher with the tandem-ovoid applicator. The mean D2cc dose for the bladder and rectum was lower with tandem-ring applicators. The clinical implication of the above dosimetric differences needs to be ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In terms of bladder doses, Ma et al [20] and Rangarajan [29] reported that there were no significant differences between TO and TR for D 2cm3 value. Similarly, statistically significant difference was not found for the same DVH parameter in the present study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In terms of bladder doses, Ma et al [20] and Rangarajan [29] reported that there were no significant differences between TO and TR for D 2cm3 value. Similarly, statistically significant difference was not found for the same DVH parameter in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…TR applicators have recently come into widespread use in IGBT of cervical cancer due to the easiness of application compared to TO applicators. Additionally, it has a predictable and fixed geometry [20,21,29]. All these physical properties of TR applicator make it more advantageous in clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations